A systematic scoping review of psychosocial and psychological factors associated with patient activation. Issue 10 (October 2020) - Golubinski, Veronika; Oppel, Eva-Maria; Schreyögg, Jonas
Highlights: This is the first literature review to examine psychosocial and psychological factors related to patient activation. We identified 21 psychosocial and psychological factors that were significantly associated with patient activation. Knowing these factors is necessary for developing and evaluating interventions to enhance patient activation. Abstract: Objective: Patient activation has been identified as an important predictor of how patients manage their own health, but little is known about its determinants. In this scoping review, we aim to address this research gap by (1) identifying literature on psychosocial/psychological factors associated with patient activation, and (2) extracting and synthesizing major results reported on that relationship. Methods: Using a systematic search of four electronic databases (Web of Science, PubMed, PsychInfo, CINAHL), our search algorithm combined related terms for "psychosocial factors" or "psychological factors" and "patient activation". Results: Of the 1128 records identified, we included 13 studies in this scoping review. In these, we identified 21 psychosocial/psychological factors that were significantly associated with patient activation. The four most frequently investigated factors were depression, self-efficacy, hope, and health status. Overall, the methodological quality of studies was low. The majority were cross sectional in design, and only one assessed causality. Conclusions: Our results suggest that psychosocial/psychological factors explain variations in patient activation. However, further research is needed to identify causal relationships between psychosocial/psychological factors and patient activation. Practice Implications: The insights from our review could be used for designing and evaluating interventions to improve patient activation.